PENGARUH KONSENTRASI SODIUM STARCH GLYCOLATE SEBAGAI SUPERDISINTEGRAN (0% DAN 20%) TERHADAP KARAKTERISTIK FISIK ORALLY DISINTEGRATING TABLET ATENOLOL - Jessica Wangsa Putri; Nani Parfati; Karina Citra Rani (CALYPTRA, 2018)
Abstract - Some geriatric patients have difficulty in swallowing tablets, resulting non-compliance issues on patient. Respond from the issues, people developed an oral dosage tablet which easily become soft and rapidly disintegrate in mouth which called orally disintegrating tablet (ODT). Atenolol is one of the anti-hypertension drugs. Atenolol is classified as antagonist selective β1 receptor class that gives the effect of anti-hypertension with low bioavailability, it is necessary to change atenolol dosage forms become ODT to increased absorption of the drug in the body. To accelerate the disintegration time (less than 3 minutes) is used disintegrant sodium starch glycolate with concentration of 0% and 20%. The method that used in the tablet’s manufacture is a direct compresssion. The result of the ODT evaluation, tablet dispersion time in vitro, wetting time , water absorption ratio, and dissolution test with its parameters include (AUC, ED and kr) were analysed statistically using one way ANOVA. There a significant difference (α = 0,05) between the formulas that using sodium starch glycolate 0% and 20% in terms of tablet’s dispersion time in vitro, wetting time, water absorption ratio, dissolution test with its parameters include (AUC, ED and kr). The formula that gives the best result is the one that using 20% disintegran sodium starch glycolate because disintegration time in 19,85±0,95 seconds, tablet’s dispersion time in vitro 29,00±1,00 seconds, wetting time 23,33±1,53 seconds, water absorption ratio 555±28,45%, TQ% 1,41 minutes, the Q% 90,64±0,44%, AUC 10134,52±29,49% minutes, ED 84,45±0,27%, and kr 0,0056/minutes.